2011
DOI: 10.1007/s00467-011-1937-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of serum myeloid-related protein 8/14 complex in Henoch–Schönlein purpura nephritis

Abstract: Myeloid-related protein (MRP) 8/14 complex is a marker of monocyte and neutrophil activation. We evaluated whether serum MRP8/14 complex is associated with clinical manifestations and pathological findings of Henoch-Schönlein purpura nephritis (HSPN). Patients were divided into two groups based on serum MRP8/14 complex levels at renal biopsy. Group 1 consisted of 18 HSPN patients with less than median (670 ng/ml) MRP8/14 complex levels, and Group 2 of 12 HSPN patients with greater than median levels. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
(22 reference statements)
1
13
1
1
Order By: Relevance
“…showed that serum S100A8/S100A9 expression reflects disease activity in ANCA‐associated vasculitis and glomerulonephritis . Furthermore, we previously reported that macrophage infiltration in glomeruli was a predictor of poor prognosis in HSPN patients . In our present study, serum MRP 8/14 levels at the first renal biopsy were higher than those at the second renal biopsy in IgAN children, and serum MRP 8/14 levels at the second biopsy in Group 2 were higher than those in Group 1.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…showed that serum S100A8/S100A9 expression reflects disease activity in ANCA‐associated vasculitis and glomerulonephritis . Furthermore, we previously reported that macrophage infiltration in glomeruli was a predictor of poor prognosis in HSPN patients . In our present study, serum MRP 8/14 levels at the first renal biopsy were higher than those at the second renal biopsy in IgAN children, and serum MRP 8/14 levels at the second biopsy in Group 2 were higher than those in Group 1.…”
Section: Discussionsupporting
confidence: 59%
“…Hirono reported that serum MRP8/14 complex levels may be a useful marker of acute Kawasaki disease activity, and the level of MRP8/14‐positive circulating endothelial cells may predict the severity of vasculitis, confirming its important role in distinct inflammatory reactions in the endothelium . With regard to serum MRP8/14 in renal disease, there have been some reports on the expression of MRP 8 and/or MRP 14 in renal tissues in patients with glomerulonephritis . Pepper et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…reviewed reports that expression of MRP8 and MRP14 on macrophages in kidneys affected by each form of GN is associated with the inflammatory activity of the GN . With regard to serum MRP8/14 in renal disease, there have been some reports on the expression of MRP 8 and/or MRP 14 in renal tissues in patients with GN …”
Section: Discussionmentioning
confidence: 99%